Use of cervical vertebral dimensions for assessment of children growth (Journal of Applied Oral Science, 2007)
OBJECTIVE: The purpose of this study was to investigate whether skeletal maturation using cephalometric radiographs could be used in a Brazilian population. MATERIAL AND METHODS: The study population was selected from the files of the Oral Radiological Clinic of the Dental School of Piracicaba, Brazil and consisted of 128 girls and 110 boys (7.0 to 15.9 years old) who had cephalometric and hand-wrist radiographs taken on the same day. Cervical vertebral bone age was evaluated using the method described by Mito and colleagues in 2002. Bone age was assessed by the Tanner-Whitehouse (TW3) method and was used as a gold standard to determine the reliability of cervical vertebral bone age. An analysis of variance and Tukey's post-hoc test were used to compare cervical vertebral bone age, bone age and chronological age at 5% significance level. RESULTS: The analysis of the Brazilian female children data showed that there was a statistically significant difference (p;0.05) was found between cervical vertebral bone age and bone age. Differently, the analysis of the male children data revealed a statistically significant difference (p